A useful gel medium for Neurospora - K. D. MUNKRES (Fungal Genetics Reports, 1990)
This note describes a useful gel medium for Neurospora with properties superior to agar-gel medium in several respects. An important property of the gel is cold-solubility which permits gentle removal of a mycelium from all types of culture vessels. Here, specific application to race tubes is described. Other merits of the gel medium will be noted.